2023
DOI: 10.1038/s41598-023-46431-2
|View full text |Cite
|
Sign up to set email alerts
|

The inverse association between DNA gaps and HbA1c levels in type 2 diabetes mellitus

Jirapan Thongsroy,
Apiwat Mutirangura

Abstract: Naturally occurring DNA gaps have been observed in eukaryotic DNA, including DNA in nondividing cells. These DNA gaps are found less frequently in chronologically aging yeast, chemically induced senescence cells, naturally aged rats, d-galactose-induced aging model rats, and older people. These gaps function to protect DNA from damage, so we named them youth-associated genomic stabilization DNA gaps (youth-DNA-gaps). Type 2 diabetes mellitus (type 2 DM) is characterized by an early aging phenotype. Here, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…The role of Box A of HMGB1 in enhancing stem cell properties of human mesenchymal cells (13) was published by our group. Recently, we also reported that decreased youth-DNA-gap numbers were observed in patients with type 2 DM and associated with increased HbA1c levels (14). The DNA gap complex is composed of Box A of high mobility group Box 1 protein (Box A), which produces a DNA gap, Sirtuin 1 (SIRT1), which deacetylates histones, and Argonaute RISC component 4 (AGO4), which methylates DNA (15,16).…”
mentioning
confidence: 99%
“…The role of Box A of HMGB1 in enhancing stem cell properties of human mesenchymal cells (13) was published by our group. Recently, we also reported that decreased youth-DNA-gap numbers were observed in patients with type 2 DM and associated with increased HbA1c levels (14). The DNA gap complex is composed of Box A of high mobility group Box 1 protein (Box A), which produces a DNA gap, Sirtuin 1 (SIRT1), which deacetylates histones, and Argonaute RISC component 4 (AGO4), which methylates DNA (15,16).…”
mentioning
confidence: 99%